Temperature-Stable 437.5 MHz Current-Starved Ring Oscillator with Bandgap Reference for Nanosatellite Beacon Transmitters - Thit Waso Khine; Lei Lei Yin Win; Khin Kyu Kyu Win; Ei Ei Khin; Mya Mya Aye (The Indonesian Institute of Science and Technology Research, 2026)
This paper presents a 437.5 MHz 3-stage CMOS current-starved ring oscillator (CSRO) with bandgap reference (BGR) design including process, voltage, and temperature (PVT) analysis. The circuit was designed and simulated in LTspice software using BSIM3 models, Level 8, 180 nm technology. The main objective is to design a simple, low-power, low-cost, high-temperature-stable (437 MHz) current-starved CMOS ring oscillator for a nanosatellite Morse code beacon transmitter. For practical implementation, the circuit was designed with standard E12 series resistor values, resulting in a final frequency of 437.5 MHz. The oscillator consumes 0.669 mW from a 1.8 V supply voltage, achieving phase noise of 95.7 dBc/Hz at 1 MHz offset and a figure-of-merit (FOM) of 150.27. The CSRO exhibits a frequency variation of 1.31% over the temperature range of -40℃ to 125℃, demonstrating excellent robustness. A supply voltage variation of 5% results in 7.02 % of frequency change. In this work, a bandgap reference circuit (BGR) was separately designed and simulated, which gave the temperature coefficient of 10.68 ppm/ across the temperature of 40 to 125 and line regulation of 0.18% across the supply voltage variation of 10%. The design includes PVT analysis across worst-case corners, temperature extremes, and ±5% supply voltage variation on operating frequency and power consumption to ensure results closely match measurements.